Trends of Blood Lead Levels in US Pregnant Women: The National Health and Nutrition Examination Survey (2001–2018) - Wang, Jing; Yang, Yujie; Zhang, Juan; Liu, Na; Xi, Huifang; Liang, Hong (Frontiers in Public Health, 2022)
Objectives This study investigates the trends of blood lead levels in US pregnant women based on the National Health and Nutrition Examination Survey from 2001 to 2018. Methods A total of 1230 pregnant women were included in this study. The weighted logistic regression was applied to analyze the association between sociodemographic characteristics with high blood levels. We computed the blood lead levels for each survey period from 2001-2002 to 2017-2018. Moreover, we used the adjusted linear regression model to investigate the time-related change in blood lead level. The odds ratio (OR) with a 95% confidence interval (CI) was calculated accordingly. Results The mean blood lead was 0.73 ± 0.03 ug/dL, and high blood lead was observed in 2.53% of individuals. The Mexican Americans were more associated with high blood lead than the non-Hispanic white (OR, 1.072; 95% CI, 1.032-1.112). The mean blood lead level has decreased from 0.97 ug/dL in 2001-2002 to 0.46 ug/dL in 2013-2014. Afterward, a slight increase was observed with the mean blood lead of 0.55 ug/dL in 2015-2016 and 0.53 ug/dL in 2017-2018. In the adjusted linear regression model, each year’s increase would lead to a 0.029 ug/dL decrease in blood lead (P < 0.001). However, no significant change was observed in the 2017-2018 cycle compared with 2009-2010 (P = 0.218). Conclusion This study summarized the trend of blood lead levels in US pregnant women over 2001-2018. Continued effort is still required to control lead sources better and protect this population from lead exposure.